Agroforestry Systems and Practices - Umrani, Ramesh (Oxford Book Company, 2012)
Agroforestry is an integrated approach of using the interactive benefits from combining trees and shrubs with crops and/or livestock. It combines agricultural and forestry technologies to create more diverse, productive, profitable, healthy and sustainable landuse systems. In agroforestry systems, trees or shrubs are intentionally used within agricultural systems, or non-timber forest resources are cultured in forest settings. Knowledge, careful selection of species and good management of trees and crops are needed to optimise the production and positive effects within the system and to minimise negative competitive effects. In some areas, a narrow definition of agroforestry might be defined as Simply: trees on farms. Hence, agroforestry, farm forestry and family forestry can be broadly understood as the commitment of farmers, alone or in partnerships, towards the establishment ~nd management of forests on their land.